2020
DOI: 10.33143/jhtm.v6i2.976
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Penggunaan Antibiotik Dengan Metode Atc/DDD Dan Du 90% Di Puskesmas Kebun Handil Kota Jambi Periode 2018 Dan 2019

Abstract: Abstrak Metode ATC / DDD merupakan metode klasifikasi dan pengukuran penggunaan obat yang saat ini telah menjadi salah satu pusat perhatian dalam pengembangan penelitian penggunaan obat. Penggunaan metode ATC/DDD dapat diintegrasikan dengan DU 90% (Drug Untilization) untuk mengidentifikasi segmen penggunaan terbanyak dalam studi penggunaan obat di suatu populasi. Penelitian ini bertujuan untuk mengetahui kuantitas penggunaan antibiotik  rawat jalan di Puskesmas Kebun Handil Kota Jambi berdasarkan metode ATC/DD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…Amoxicillin is the first-choice antibiotic given for pharyngitis, which is one of the reasons for its high use (Departemen Kesehatan RI, 2005). These outcomes are in line with studies carried out by (Amesta, 2021) and (Gusdilla, 2019), where amoxicillin has the highest DDD value compared to other antibiotics.…”
Section: Quantitative Use Of Antibioticssupporting
confidence: 90%
“…Amoxicillin is the first-choice antibiotic given for pharyngitis, which is one of the reasons for its high use (Departemen Kesehatan RI, 2005). These outcomes are in line with studies carried out by (Amesta, 2021) and (Gusdilla, 2019), where amoxicillin has the highest DDD value compared to other antibiotics.…”
Section: Quantitative Use Of Antibioticssupporting
confidence: 90%
“…interactions, adjusting the drug dose given to patients for two or more interacting drugs, giving a break of 2 hours before or 4 hours after Drugs that trigger interactions are given if they interact during the absorption phase. In this study, the severity of drug interactions was not found in the pulveres prescription sheet 19,20.…”
mentioning
confidence: 57%
“…There were 20 reports (5 193 626 patients) that reported data on antibiotic consumption, of which 16 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 in inpatients and four 34 , 35 , 36 , 37 in outpatients. Most of these studies were conducted in hospital settings (16 reports, 76.2%), in Java (14 reports, 66.7%), and between 2016-2021 (17 reports, 81.0%; Table S4).…”
Section: Resultsmentioning
confidence: 99%